2017
DOI: 10.3390/economies5020017
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Institutional Factors and FDI Flows in Developing Countries: New Evidence from Dynamic Panel Estimation

Abstract: Abstract:In this paper, we revisit the relation between institutional factors and foreign direct investment (FDI) inflows in developing countries by employing a dynamic panel methodology, which enables us to deal with the persistency of FDI flows and endogeneity issues. We also contribute to the literature by using various measures of institutions to identify which aspects of institutional quality affect FDI in the developing world. Our empirical findings based on 113 developing countries over the period [2002… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
40
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(68 citation statements)
references
References 42 publications
8
40
0
3
Order By: Relevance
“…This estimator resolves some of the small-sample biases of the standard GMM estimator without enforcing particularly strong assumptions [53]. This estimator creates a system of two equations; the first equation is differenced while the second one remains in levels [54]. Also, in addition to the corrections for serial correlations, measurement error and endogeneity also accounted for the underlying data dynamics [55].…”
Section: Econometric Model and Estimation Methodsmentioning
confidence: 99%
“…This estimator resolves some of the small-sample biases of the standard GMM estimator without enforcing particularly strong assumptions [53]. This estimator creates a system of two equations; the first equation is differenced while the second one remains in levels [54]. Also, in addition to the corrections for serial correlations, measurement error and endogeneity also accounted for the underlying data dynamics [55].…”
Section: Econometric Model and Estimation Methodsmentioning
confidence: 99%
“…Such as, Gangi and Abdulrazak (2012) showed a positive relationship between voice and accountability and inward FDI. Similarly, Kurul and Yalta (2017) used the dynamic panel approach on 113 developing countries and concluded that voice and accountability has a positive and significant impact on FDI inflows. Moreover, Aidt, Dutta and Sena (2008) argue that if there is proper accountability of the politicians in a country, it reduced corruption, and thus FDI is increased.…”
Section: Voice and Accountability And Fdimentioning
confidence: 99%
“…Using OLS or fixed effect model we have to admit that results are potentially inconsistent and biased due to endogeneity problem between independent and explanatory variables. The endogeneity problem can be reducing by adopting the instrumental variables (IV) approach Kurul & Yalta (2017). But due to weak instruments the OLS approach estimators are likely to be biased to similar to fixed effect (FE) estimator.…”
Section: Main Modelsmentioning
confidence: 99%